Réponses

2013-10-19T18:00:30+02:00
 A = [-5-(-8)]x(-2)= [-5+8]x(-2)                           = 3 x (-2) = -9    B= 26-(-9)x1,5-0,5= 26-(-13.5) -0.5                             = 26 +13.5 -0.5                             = 26 + 13 = 39   C=26:(-3-2x5)= 26: (-3-10)                     = 26: (-13)= -2  
A = [-5-(-8)]x(-2)= [-5+8]x(-2)

= 3 x (-2) = -9
B= 26-(-9)x1,5-0,5= 26-(-13.5) -0.5

= 26 +13.5 -0.5

= 26 + 13 = 39
C=26:(-3-2x5)= 26: (-3-10)

= 26: (-13)= -2
2013-10-19T18:07:36+02:00
A= [-5-(-8)]*(-2) 
= 3 * (-2)
= -6

B=26-(-9)*1.5-0.5
= 26 + 13,5 - 0,5
= 39,5 - 0,5
= 39

C=26/(-3-2*5)
= 26 / ( -3 - 10 )
= 26 / (-13)
= -2